How to improve filter throughput

A polishing liquid composition with silica particles and an amino group-containing polymer at specific pH and pKa conditions addresses filter clogging and surface defects, enhancing filter flow rate and silicon substrate quality for semiconductor manufacturing.

JP7606314B2Active Publication Date: 2024-12-25KAO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020171485
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-09
Publication Date
2024-12-25
Estimated Expiration
2040-10-09

AI Technical Summary

Technical Problem

The clogging of filters during the filtration of polishing liquid compositions containing silica particles and the occurrence of surface defects on silicon substrates due to agglomeration of silica particles, which affect the filter flow rate and surface quality, are unresolved issues in semiconductor manufacturing.

Method used

A method involving a polishing liquid composition with silica particles and an amino group-containing water-soluble polymer, maintained at a pH between 8.5 and 14, and a pKa difference of 2 or more, is used to improve the filter flow rate and reduce surface defects on silicon substrates.

Benefits of technology

The method enhances the amount of polishing liquid composition passing through a 0.2 μm filter and improves the surface quality of silicon substrates by reducing light point defects (LPD), thereby supporting high-yield, cost-effective semiconductor substrate manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606314000001
    Figure 0007606314000001
  • Figure 0007606314000002
    Figure 0007606314000002
  • Figure 0007606314000003
    Figure 0007606314000003
Patent Text Reader

Abstract

To provide methods that can increase the volume of a polishing liquid composition containing silica particles passed through a filter, and / or, can also improve the surface quality of a silicon substrate after polishing (reduction in LPD).SOLUTION: The present invention discloses a method that increases the volume of a polishing liquid composition passed through a filter, the method including preparing a polishing liquid composition that contains silica particles (component A) and amino group-containing water-soluble polymers (component B), with a pH of more than 8.5 to 14 or less, and the component B having a difference between pKa and pH (pH-pKa) of 2 or more. The present invention also discloses a method that improves the surface quality of a silicon substrate after polishing, the method including polishing a silicon substrate of interest by using polishing liquid composition that contains component A and component B with a pH of more than 8.5 to 14 or less, and the component B having a difference between pKa and pH (pH-pKa) of 2 or more. The present invention also discloses a method that polishes a silicon substrate, the method including the step of polishing a silicon substrate of interest by using polishing liquid composition that contains component A and component B with a pH of more than 8.5 to 14 or less, and the component B having a difference between pKa and pH (pH-pKa) of 2 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for improving the filter passage amount of a polishing composition containing silica particles. [Background technology]

[0002] In recent years, the demand for higher storage capacity of semiconductor memory has led to the trend toward finer design rules for semiconductor devices. As a result, the depth of focus in photolithography used in the manufacturing process of semiconductor devices has become shallower, and the demands for reduced defects and smoothness of silicon substrates (bare wafers) have become increasingly strict.

[0003] Polishing compositions containing silica particles are known as polishing compositions used for polishing silicon substrates. In this type of polishing composition, problems arise such as the occurrence of surface defects (LPD: Light Point Defects) on the silicon substrate caused by the aggregation of silica particles, and filter clogging when filtering the polishing composition to remove the aggregates (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-109423 A Summary of the Invention [Problem to be solved by the invention]

[0005] There is a demand for a method for reducing clogging when a polishing composition containing silica particles is filtered through a filter and increasing the amount of liquid passing through the filter, as well as a method for reducing surface defects on a polished silicon substrate and improving surface quality.

[0006] The present disclosure provides a method that enables an improvement in the filter pass-through amount of a polishing composition containing silica particles and / or an improvement in the surface quality of a polished silicon substrate (reduction in LPD). [Means for solving the problem]

[0007] In one aspect, the present disclosure relates to a method for improving the flow rate of a polishing liquid composition containing silica particles through a filter with a pore size of 0.2 μm, the method including preparing a polishing liquid composition by blending silica particles (component A) and an amino group-containing water-soluble polymer (component B) and having a pH of more than 8.5 and not more than 14, and having a difference (pH-pKa) between the pKa of component B and the pH of the composition of more than 2.

[0008] In one aspect, the present disclosure relates to a method for improving the surface quality of a polished silicon substrate, the method comprising polishing a silicon substrate with a polishing liquid composition that contains silica particles (component A) and an amino group-containing water-soluble polymer (component B), has a pH of more than 8.5 and not more than 14, and has a difference between the pKa of component B and the pH (pH-pKa) of 2 or more.

[0009] In one aspect, the present disclosure relates to a method for polishing a silicon substrate, comprising a step of polishing a silicon substrate to be polished with a polishing liquid composition, the polishing liquid composition comprising silica particles (component A) and an amino group-containing water-soluble polymer (component B), having a pH of more than 8.5 and not more than 14, and a difference between the pKa and the pH of component B (pH-pKa) of 2 or more.

[0010] In one aspect, the present disclosure relates to a polishing liquid composition comprising silica particles (component A) and an amino group-containing water-soluble polymer (component B), having a pH greater than 8.5 and not greater than 14, and a difference between the pKa of component B and the pH (pH-pKa) of 2 or more.

[0011] In one aspect, the present disclosure relates to a method for producing a semiconductor substrate, the method including the steps of polishing a silicon substrate to be polished using the polishing method of the present disclosure, and cleaning the polished silicon substrate. Effect of the Invention

[0012] According to the present disclosure, it is possible to provide a method for improving the filter pass-through amount of a polishing composition containing silica particles. The present disclosure can provide a method for improving the surface quality (reducing LPD) of a polished silicon substrate. The present disclosure can provide a method for polishing a silicon substrate using a polishing composition that contains silica particles and that can improve the filter passing amount of the polishing composition and / or the surface quality of the polished silicon substrate (reduce LPD). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The method disclosed herein is based on the finding that the filter pass-through amount of a polishing composition containing silica particles (component A) can be improved by adding a specific amino group-containing water-soluble polymer (component B) to the polishing composition. The method disclosed herein is based on the finding that the surface quality of polished silicon substrates can be improved (LPD can be reduced) by using a polishing composition that contains, in addition to silica particles (component A), a specific amino group-containing water-soluble polymer (component B). The method disclosed herein is based on the finding that by using a polishing liquid composition that contains a specific amino group-containing water-soluble polymer (component B) in addition to silica particles (component A), it is possible to improve the filter pass-through amount of the polishing liquid composition containing silica particles and / or the surface quality of the polished silicon substrate (reducing LPD).

[0014] Although the details of the mechanism by which the method of the present disclosure exerts its effect are not clear, it is presumed as follows. Under alkaline polishing conditions with a pH greater than 8.5 and equal to or less than 14, both the silica abrasive grains and the silicon substrate to be polished have negative charges, and electrostatic repulsion is always generated. In order to improve the polishing rate, it is effective to alleviate this electrostatic repulsion, and the negative charges on both surfaces can be alleviated by using a cationic substance, but since the cationic substance is adsorbed by electrostatic interaction, aggregation occurs between the silica particles, which gives rise to a new problem of clogging when the polishing composition is filtered through a filter. Therefore, when water-soluble polymers having amino groups are focused on, cationicity is reduced in the amino group-containing water-soluble polymer (component B) whose pKa is 2 or more lower than the pH of the polishing liquid. As a result, the amino group-containing water-soluble polymer (component B) is adsorbed to the silica particles (component A) by van der Waals force, suppressing aggregation between silica particles, so that the average particle size ratio d / d0 of the silica particles is 1.1 or less, and the amount of liquid passing through the polishing liquid composition containing silica particles is improved even when a filter with a pore size of 0.2 μm is used. Furthermore, it is considered that the reduction in aggregated particles can reduce the LPD of the polished silicon substrate and improve the surface quality. However, the present disclosure need not be construed as being limited to these mechanisms.

[0015] In the present disclosure, improving the surface quality of a polished silicon substrate, in one or more embodiments, is reducing the number of surface defects (LPDs) in the polished substrate.

[0016] [Methods for improving filter throughput] In one aspect, the method disclosed herein relates to a method for improving the flow rate of a polishing liquid composition containing silica particles through a filter with a pore size of 0.2 μm, the method comprising blending silica particles (component A) and an amino group-containing water-soluble polymer (component B) to prepare a polishing liquid composition having a pH greater than 8.5 and not greater than 14, and in which the difference between the pKa of component B and the pH (pH-pKa) is 2 or more (hereinafter also referred to as the “method of this aspect 1”). According to the method of this embodiment 1, by using the polishing liquid composition, clogging of a filter during filter treatment before use or filter treatment for cyclic use can be suppressed, and the amount of liquid passing through a filter with a pore size of 0.2 μm can be improved. In addition, preferred embodiments of Component A, Component B, and the polishing composition in this embodiment 1 are as described below.

[0017] [Filter and flow rate] The material of the filter used in the method of this embodiment 1 is not particularly limited, but examples include polytetrafluoroethylene (PTFE), nylon 66, polypropylene, polyethersulfone, polysulfone, mixed cellulose esters, cellulose acetate, and the like. Among these, from the viewpoint of alkali resistance, at least one selected from polytetrafluoroethylene, polypropylene, polytetrafluoroethylene, polyethersulfone, and polysulfone is preferred. The structure of the filter used in the method of this embodiment 1 is not particularly limited, but examples include a single-layer porous (membrane), a multi-layer nonwoven fabric (depth), or a combination thereof, and of these, a single-layer porous (membrane) is preferred from the viewpoint of filtration accuracy.

[0018] The filtration pressure in the method of this embodiment 1 is preferably 0.1 MPa or more, more preferably 0.2 MPa or more, from the viewpoint of improving the amount of liquid passing through, and is preferably 5 MPa or less, more preferably 1 MPa or less, and even more preferably 0.5 MPa or less, from the viewpoint of device durability. The filtration pressure can be adjusted by the liquid sending speed when the liquid is sent by a pump, or by air pressure when pressure is applied by air, but is preferably adjusted by air pressure.

[0019] The amount of liquid passing through the 0.2 μm pore size filter used in the method of the present embodiment 1 (g / cm 2 In one or more embodiments, the viscosity is 10 g / cm 2 ·min or more, 25g / cm 2 ·min or more, 40g / cm 2 ·min or more, 50g / cm 2 ·min or more, 60g / cm 2 10 minutes or more, or 70g / cm 2 The amount of liquid passing through a 0.2 μm pore size filter can be measured by the method described in the Examples.

[0020] The filter used in the method of the present embodiment 1 is not particularly limited, but may be, for example, a filter with a pore size of 0.2 μm and a filtration area of ​​4 cm 2A filter such as that described above (Advantec Corporation, hydrophilic PTFE 0.2 μm (pore size) filter, model: 25HP020AN) can be used.

[0021] The method for measuring the amount of liquid passing through the filter is not particularly limited. The polishing composition is placed in a container or syringe equipped with a filter, and the polishing composition is passed through the filter by applying pressure or pressure, and the amount of liquid passing through the filter until the filter becomes clogged (g / sec cm 2 ) can be measured.

[0022] [Methods for improving surface quality (reducing LPD)] In one aspect, the method disclosed herein relates to a method for improving the surface quality of a polished silicon substrate, the method comprising polishing a silicon substrate to be polished with a polishing liquid composition that contains silica particles (component A) and an amino group-containing water-soluble polymer (component B), has a pH greater than 8.5 and not greater than 14, and has a difference between the pKa of component B and the pH (pH-pKa) of 2 or more (hereinafter also referred to as the “method of this aspect 2”). According to the method of the present embodiment, the surface quality of the polished substrate can be improved by using the polishing composition. The improvement in surface quality can include a reduction in LPD, which is a defect on the substrate surface after polishing. In addition, preferred embodiments of Component A, Component B, and the polishing composition in this embodiment 2 are as described below.

[0023] [Silicon substrate polishing method] In one aspect, the method disclosed herein relates to a method for polishing a silicon substrate, comprising a step of polishing a silicon substrate to be polished with a polishing liquid composition (hereinafter also referred to as a "polishing step"), in which the polishing liquid composition comprises silica particles (component A) and an amino group-containing water-soluble polymer (component B), has a pH greater than 8.5 and less than or equal to 14, and the difference between the pKa and the pH (pH-pKa) of component B is 2 or greater (hereinafter also referred to as a "method of this aspect 3" or a "polishing method of the present disclosure"). According to the method of the present embodiment 3, the above-mentioned polishing composition is used, so that it is possible to improve the filter passing amount of the polishing composition containing silica particles and the surface quality of the polished silicon substrate. In addition, preferred embodiments of Component A, Component B, and the polishing composition in this embodiment 3 are as described below.

[0024] In the polishing step of the polishing method of the present disclosure, for example, the silicon substrate can be pressed against a platen to which a polishing pad is attached, and the silicon substrate can be polished at a polishing pressure of 3 to 20 kPa. In the present disclosure, the polishing pressure refers to the pressure of the platen applied to the surface of the silicon substrate during polishing.

[0025] In the polishing step of the polishing method of the present disclosure, for example, a silicon substrate to be polished can be pressed against a platen to which a polishing pad is attached, and the silicon substrate to be polished can be polished with a polishing liquid composition and a polishing pad surface temperature of 15° C. to 40° C. From the viewpoint of achieving both an improvement in the polishing rate and surface quality such as a reduction in surface roughness (haze), the temperature of the polishing liquid composition and the polishing pad surface temperature are preferably 15° C. or higher or 20° C. or higher, and preferably 40° C. or lower or 30° C. or lower.

[0026] [Polished silicon substrate] The polishing liquid composition used in the method of the present disclosure (hereinafter also referred to as "polishing liquid composition of the present disclosure") is a polishing composition for silicon substrates, and can be used, for example, in a polishing step of polishing a silicon substrate to be polished in a manufacturing method of a semiconductor substrate, or in a polishing step of polishing a silicon substrate to be polished in a polishing method of a silicon substrate. In one or more embodiments, the silicon substrate to be polished using the polishing liquid composition of the present disclosure may be a silicon substrate, and in one or more embodiments, a single crystal silicon substrate, a polysilicon substrate, a substrate having a polysilicon film, a SiN substrate, etc. are examples. From the viewpoint of exerting the effect of the polishing liquid composition of the present disclosure, a single crystal silicon substrate or a polysilicon substrate is preferred, and a single crystal silicon substrate is more preferred.

[0027] [Polishing liquid composition] In one or a plurality of embodiments, the polishing liquid composition of the present disclosure contains silica particles (component A) and an amino group-containing water-soluble polymer (component B), has a pH greater than 8.5 and not greater than 14, and has a difference between the pKa and the pH (pH-pKa) of component B of at least 2. According to the polishing liquid composition of the present disclosure, the amount of liquid passing through a 0.2 μm pore size filter is improved, and / or the LPD of a polished silicon substrate is reduced, thereby improving the surface quality.

[0028] [Silica particles (component A)] The polishing composition of the present disclosure contains silica particles (hereinafter also referred to as "component A") as an abrasive. Examples of component A include colloidal silica, fumed silica, pulverized silica, and surface-modified silica thereof. From the viewpoint of improving the filter passing amount of the polishing composition containing silica particles and from the viewpoint of improving the surface quality of the silicon substrate after polishing, colloidal silica is preferred. Component A may be one type or a combination of two or more types.

[0029] From the viewpoint of operability, the use form of component A is preferably a slurry form.When component A contained in the polishing liquid composition of the present disclosure is colloidal silica, from the viewpoint of preventing contamination of silicon substrate by alkali metal, alkaline earth metal, etc., the colloidal silica is preferably obtained from the hydrolysis product of alkoxysilane.The silica particles obtained from the hydrolysis product of alkoxysilane can be produced by a conventionally known method.

[0030] From the viewpoint of maintaining the polishing rate, the average primary particle diameter of component A is preferably 10 nm or more, more preferably 15 nm or more, even more preferably 20 nm or more, and more preferably 30 nm or more, and from the viewpoint of improving the filter passing amount of the polishing composition containing silica particles and the surface quality of the polished silicon substrate, it is preferably 50 nm or less, more preferably 45 nm or less, and even more preferably 40 nm or less. From the same viewpoint, the average primary particle diameter of component A is preferably 10 nm or more and 50 nm or less, more preferably 15 nm or more and 45 nm or less, and even more preferably 20 nm or more and 40 nm or less. In the present disclosure, the average primary particle size of component A is determined by the specific surface area S (m 2 The average primary particle size is calculated using the formula (1 / g). The average primary particle size is a value measured by the method described in the Examples.

[0031] From the viewpoint of maintaining the polishing rate, the average secondary particle diameter of component A is preferably 20 nm or more, more preferably 30 nm or more, and even more preferably 40 nm or more, and from the viewpoint of improving the filter passing amount of the polishing composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate, it is preferably 100 nm or less, more preferably 90 nm or less, and even more preferably 80 nm or less. From the same viewpoint, the average secondary particle diameter of component A is preferably 20 nm or more and 100 nm or less, more preferably 30 nm or more and 90 nm or less, and even more preferably 40 nm or more and 80 nm or less. In the present disclosure, the average secondary particle size is a value measured by a dynamic light scattering (DLS) method, and is a value measured by the method described in the Examples.

[0032] From the viewpoint of improving the filter pass-through amount of the polishing composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate, the degree of association of component A is preferably 3 or less, more preferably 2.5 or less, and even more preferably 2.3 or less, and from the same viewpoints, it is preferably 1.1 or more, more preferably 1.5 or more, and even more preferably 1.8 or more.

[0033] In the present disclosure, the degree of association of component A is a coefficient representing the shape of the silica particles and is calculated by the following formula. Degree of association = average secondary particle diameter / average primary particle diameter

[0034] The degree of association of Component A can be adjusted by using the methods described in, for example, JP-A-6-254383, JP-A-11-214338, JP-A-11-60232, JP-A-2005-060217, JP-A-2005-060219, and the like.

[0035] The shape of component A is preferably a so-called spherical shape and / or a so-called cocoon shape from the viewpoint of improving the filter passing amount of the polishing composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate.

[0036] The content of component A in the polishing liquid composition of the present disclosure is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and even more preferably 0.1 mass% or more, calculated as SiO2, from the viewpoint of improving the filter passing amount of the polishing liquid composition containing silica particles and from the viewpoint of improving the surface quality of the silicon substrate after polishing. From the same viewpoint, it is preferably 2.5 mass% or less, more preferably 1 mass% or less, more preferably 0.8 mass% or less, even more preferably 0.5 mass% or less, and even more preferably 0.3 mass% or less. The content of component A in the polishing liquid composition of the present disclosure is preferably 0.01 mass% or more and 2.5 mass% or less, more preferably 0.05 mass% or more and 1 mass% or less, more preferably 0.05 mass% or more and 0.8 mass% or less, more preferably 0.05 mass% or more and 0.5 mass% or less, and even more preferably 0.1 mass% or more and 0.3 mass% or less. When component A is a combination of two or more kinds, the content of component A refers to the total content thereof.

[0037] [Amino group-containing water-soluble polymer (component B)] The polishing liquid composition of the present disclosure contains an amino group-containing water-soluble polymer (hereinafter also referred to as "component B"). It is believed that component B can adjust the zeta potential of the silica particles (component A) and suppress the aggregation of the silica particles. In the present disclosure, "water-soluble" means having a solubility of 0.5 g / 100 mL or more in water (20° C.), preferably a solubility of 2 g / 100 mL or more.

[0038] From the viewpoint of improving the filter pass-through amount of the polishing liquid composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate, the pKa of component B is preferably 5 or more, more preferably 5.5 or more, even more preferably 5.9 or more, and even more preferably 6.3 or more, and from the same viewpoint, it is preferably lower than the pH of the polishing liquid composition, and is preferably 8.5 or less, more preferably 8.3 or less, even more preferably 8.1 or less, and even more preferably 8 or less. Furthermore, when component B is component B1 described below, the pKa of component B is more preferably 6.5 or more, and more preferably 7.7 or less, more preferably 7.4 or less, and more preferably 7.1 or less. Furthermore, when component B is component B2 described later, the pKa of component B is more preferably 6.6 or more, more preferably 6.9 or more, more preferably 7.1 or more, and more preferably 7.8 or less, more preferably 7.6 or less, and more preferably 7.4 or less.

[0039] From the viewpoint of improving the filter passing amount of the polishing composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate, it is preferable that component B contains one or more monomer-derived constitutional units selected from allylamine and diallylamine. From the viewpoint of availability, in one or more embodiments, component B is preferably an amino group-containing water-soluble polymer containing an allylamine-derived constitutional unit (hereinafter also referred to as "component B1"), and in one or more embodiments, it is preferably an amino group-containing water-soluble polymer containing a diallylamine-derived constitutional unit (hereinafter also referred to as "component B2").

[0040] (Component B1: Amino group-containing water-soluble polymer containing structural units derived from allylamine) In one or more embodiments, at least a part of the amino groups in the allylamine-derived structural unit preferably has a steric shielding group from the viewpoint of improving the filter passing amount of the polishing composition containing silica particles, from the viewpoint of improving the surface quality of the polished silicon substrate, and from the viewpoint of availability. In the present disclosure, the steric shielding group refers to a three-dimensional (bulky) substituent that can shield the nitrogen atom of the amino group of component B to suppress cationization, that is, to lower the pKa. From the same viewpoint, the amino group having the steric shielding group is preferably a secondary amino group or a tertiary amino group containing a hydrocarbon group having 3 to 11 carbon atoms and a hydroxyl group. The number of carbon atoms in the hydrocarbon group is preferably 3 or more from the viewpoints of improving the shielding ability of the amino group (suppressing cationization of the nitrogen atom of the amino group), improving the filter passing amount of the polishing liquid composition containing silica particles, and improving the surface quality of the polished silicon substrate, and from the viewpoints of improving water solubility and availability, the number of carbon atoms is preferably 11 or less, more preferably 7 or less, even more preferably 5 or less, and even more preferably 4 or less.

[0041] In one or more embodiments, the amino group having a steric shielding group is a modified group of an amino group by a glycidol derivative, and in one or more embodiments, is a group formed by reacting an amino group in a structural unit derived from allylamine with a glycidol derivative. At least a part of the amino groups among all the amino groups of component B1 is modified by the glycidol derivative to become an amino group having a steric shielding group. The equivalent of the glycidol derivative relative to the number of amino groups (1 equivalent) in the allylamine-derived structural unit (hereinafter also referred to as the "glycidol modification rate") is preferably 0.3 or more, more preferably 0.5 or more, even more preferably 0.8 or more, even more preferably 1 or more, preferably more than 1.1, more preferably 1.2 or more, even more preferably 1.3 or more, even more preferably 1.4 or more, even more preferably 1.5 or more, even more preferably 1.7 or more, and from the same viewpoints, it is preferably 4 or less, more preferably 3 or less, even more preferably 2.5 or less, and even more preferably 2 or less.

[0042] In the present disclosure, the glycidol modification rate is 13 The glycidol modification rate is a value measured by the method described in the Examples using C-NMR, however, the glycidol modification rate can also be measured by the following method (1) or (2). (1) It can be calculated from the amino group equivalent of the allylamine polymer and the number of moles of the glycidol derivative used as the reaction raw material. (2) The nitrogen content N (mass%) of the reaction product of a glycidol derivative and an allylamine polymer is measured, and the nitrogen content N can be calculated from the following formula. Glycidol modification rate = A / B Here, A=(100-N×molecular weight of allylamine monomer / 14) / molecular weight of glycidol derivative, and B=N / 14.

[0043] Examples of the glycidol derivative include glycidol and alkyl glycidyl ether, and glycidol is preferred from the viewpoint of availability, improving the amount of the polishing liquid composition containing silica particles passing through a filter, and improving the surface quality of the polished silicon substrate. The alkyl group of the alkyl glycidyl ether is preferably an alkyl group having 1 to 8 carbon atoms from the viewpoint of availability, and examples of the alkyl group include methyl, ethyl, propyl, butyl, and 2-ethylhexyl. Examples of the alkyl glycidyl ether include methyl glycidyl ether and 2-ethylhexyl glycidyl ether.

[0044] In one or more embodiments, component B1 may be a polyallylamine in which at least a portion of amino groups has a sterically shielding group, and in one or more embodiments, may be a reaction product of a polyallylamine with a glycidol derivative.

[0045] In one or more embodiments, Component B1 may be a compound containing a structural unit represented by the following formula (I) (glycidol-modified polyallylamine). [ka]

[0046] In formula (I), R 1 and R 2 are each a hydrogen atom or a sterically shielding group. Examples of the sterically shielding group include a modifying group derived from a glycidol derivative, and in one or more embodiments, a 1-molar or 2-molar adduct of glycidol is included, and in one or more embodiments, examples include -CH2CH(OH)CH2(OH), -CH2CH(OH)CHO-CH2CH(OH)CH2(OH), and the like.

[0047] (Component B2: Amino group-containing water-soluble polymer containing a constitutional unit derived from diallylamine) In one or more embodiments, at least a part of the amino groups in the diallylamine-derived constitutional unit preferably has an electron-withdrawing group at the β- or γ-position of the amino group, from the viewpoint of improving the filter passing amount of the polishing composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate. Examples of the electron-withdrawing group include a group represented by the following formula (II).

[0048] [ka]

[0049] In one or more embodiments, component B2 includes a compound containing a diallylamine-derived constituent unit and a sulfur dioxide-derived constituent unit, for example, a compound containing a constituent unit represented by the following formula (III). [ka]

[0050] In formula (III), R 3 is an alkyl group having 1 to 3 carbon atoms which may have a hydroxyl group. From the viewpoint of availability and economic efficiency, R 3 is preferably a methyl group. Also, n+m=1, and n and m are 0 or 1. From the same viewpoint, a compound where m=1 and n=0 is preferred. A mixture of a compound where m=1 and n=0 and a compound where m=0 and n=1 may also be used.

[0051] In one or more embodiments, Component B2 includes a compound containing a constituent unit represented by the following formula (IV), such as a methyldiallylamine / sulfur dioxide copolymer. [ka]

[0052] From the viewpoint of improving the filter passing amount of the polishing composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate, the weight average molecular weight of component B is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, and even more preferably 2,000 or more, and from the same viewpoint, it is preferably 100,000 or less, more preferably 50,000 or less, even more preferably 30,000 or less, even more preferably 20,000 or less, even more preferably 15,000 or less, and even more preferably 12,000 or less. The weight average molecular weight of component B in the present disclosure can be measured, for example, by the method described in the Examples.

[0053] When component B is component B1, the weight average molecular weight of component B is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, even more preferably 2,000 or more, preferably 3,000 or more, more preferably 5,000 or more, even more preferably 6,000 or more, even more preferably 7,000 or more, and from the same viewpoints, it is preferably 100,000 or less, more preferably 50,000 or less, even more preferably 30,000 or less, even more preferably 20,000 or less, even more preferably 15,000 or less, even more preferably 12,000 or less.

[0054] When component B is component B2, the weight average molecular weight of component B is preferably 800 or more, more preferably 1,000 or more, even more preferably 1,500 or more, and even more preferably 2,000 or more, from the viewpoint of improving the filter pass-through amount of the polishing liquid composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate, and from the similar viewpoints, it is preferably 100,000 or less, more preferably 50,000 or less, even more preferably 30,000 or less, even more preferably 20,000 or less, even more preferably 15,000 or less, even more preferably 12,000 or less, even more preferably 10,000 or less, even more preferably 7,000 or less, even more preferably 5,000 or less, and even more preferably 4,000 or less.

[0055] The content of component B in the polishing composition of the present disclosure is preferably 10 mass ppm or more, more preferably 20 mass ppm or more, and even more preferably 30 mass ppm or more from the viewpoint of improving the filter passing amount of the polishing composition containing silica particles and the surface quality of the polished silicon substrate, and from the same viewpoint, is preferably 200 mass ppm or less, more preferably 150 mass ppm or less, and even more preferably 120 mass ppm or less. In the present disclosure, 1 mass% is 10,000 mass ppm (the same applies below).

[0056] The ratio of the content of component B to the content of component A in the polishing liquid composition of the present disclosure (mass ratio B / A) is preferably 0.008 or more, more preferably 0.016 or more, and even more preferably 0.025 or more, from the viewpoint of improving the filter pass-through amount of the polishing liquid composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate, and from the similar viewpoints, is preferably 0.2 or less, preferably 0.16 or less, more preferably 0.12 or less, and even more preferably 0.09 or less.

[0057] [Adsorption amount] In the polishing composition of the present disclosure, the amount (%) of component B adsorbed to component A is preferably more than 50%, more preferably 51% or more, and even more preferably 55% or more, from the viewpoint of improving the filter passing amount of the polishing composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate. From the same viewpoint, the amount (%) of adsorption is preferably 95% or less, more preferably 90% or less, and even more preferably 85% or less. The amount (%) of component B adsorbed to component A can be calculated by the method described in the Examples.

[0058] [Average particle size ratio of silica particles d / d0] In the polishing liquid composition of the present disclosure, from the viewpoint of improving the filter pass-through amount of the polishing liquid composition containing silica particles, and from the viewpoint of improving the surface quality of the polished silicon substrate, the average particle size ratio d / d0 of the silica particles calculated from d and d0 defined as follows is preferably 1.1 or less, more preferably 1.08 or less, even more preferably 1.05 or less, and even more preferably 1.04 or less. d: average particle size of silica particles in the polishing composition d0: average particle size of silica particles in the polishing composition having the same pH value but excluding the amino group-containing water-soluble polymer In the present disclosure, the average particle size d and the average particle size d0 are values ​​measured by dynamic light scattering, and are values ​​measured by the method described in the Examples.

[0059] [water] In one or more embodiments, the polishing liquid composition of the present disclosure may contain water. Examples of water include ion-exchanged water and ultrapure water. The content of water in the polishing liquid composition of the present disclosure may be, for example, the remainder of component A, component B, and any optional components described below.

[0060] [Nitrogen-containing basic compound (component C)] In one or more embodiments, the polishing liquid composition of the present disclosure preferably further contains a nitrogen-containing basic compound (hereinafter also referred to as "component C") from the viewpoint of adjusting the pH. Component C is preferably a water-soluble nitrogen-containing basic compound from the viewpoint of achieving both improved polishing rate and storage stability, and from the viewpoint of improving surface quality. In the present disclosure, "water-soluble nitrogen-containing basic" refers to a nitrogen-containing compound that exhibits basicity when dissolved in water. In one or more embodiments, component C does not include an amino group-containing water-soluble polymer (component B). Component C may be one type or a combination of two or more types.

[0061] In one or more embodiments, component C may be at least one selected from an amine compound and an ammonium compound. For example, component C may be one or a combination of two or more selected from ammonia, ammonium hydroxide, ammonium carbonate, ammonium hydrogen carbonate, dimethylamine, trimethylamine, diethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, N-methylethanolamine, N-methyl-N,N-diethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, N,N-dibutylethanolamine, N-(β-aminoethyl)ethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, ethylenediamine, hexamethylenediamine, piperazine hexahydrate, anhydrous piperazine, 1-(2-aminoethyl)piperazine, N-methylpiperazine, diethylenetriamine, tetramethylammonium hydroxide, and hydroxylamine. Among these, from the viewpoint of improving the filter passing amount of the polishing composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate, ammonia or a mixture of ammonia and hydroxyamine is preferred as component C, and ammonia is more preferred.

[0062] When the polishing liquid composition of the present disclosure contains component C, the content of component C in the polishing liquid composition of the present disclosure is preferably 5 mass ppm or more, more preferably 10 mass ppm or more, and even more preferably 20 mass ppm or more from the viewpoint of improving the filter passing amount of the polishing liquid composition containing silica particles and from the viewpoint of improving the surface quality of the silicon substrate after polishing, and from the same viewpoint and from the viewpoint of suppressing corrosion of the silicon substrate, it is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, more preferably 150 mass ppm or less, and even more preferably 100 mass ppm or less. From the same viewpoint, the content of component C in the polishing liquid composition of the present disclosure is preferably 5 mass ppm or more and 500 mass ppm or less, more preferably 10 mass ppm or more and 300 mass ppm or less, more preferably 20 mass ppm or more and 150 mass ppm or less, and even more preferably 20 mass ppm or more and 100 mass ppm or less. When component C is a combination of two or more kinds, the content of component C refers to the total content thereof.

[0063] When the polishing liquid composition of the present disclosure contains component C, the ratio C / A (mass ratio C / A) of the content of component C to the content of component A in the polishing liquid composition of the present disclosure is preferably 0.002 or more, more preferably 0.01 or more, even more preferably 0.015 or more, and even more preferably 0.025 or more, from the viewpoint of improving the filter passing amount of the polishing liquid composition containing silica particles and from the viewpoint of improving the surface quality of the silicon substrate after polishing, and from the same viewpoint and from the viewpoint of suppressing corrosion of the silicon substrate, it is preferably 1 or less, more preferably 0.5 or less, even more preferably 0.1 or less, and even more preferably 0.08 or less. From the same viewpoint, the mass ratio C / A in the polishing liquid composition of the present disclosure is preferably 0.002 or more and 1 or less, more preferably 0.01 or more and 0.5 or less, even more preferably 0.015 or more and 0.1 or less, and even more preferably 0.025 or more and 0.08 or less.

[0064] [Other ingredients] The polishing liquid composition of the present disclosure may further contain other components to the extent that the effects of the present disclosure are not impaired. In one or more embodiments, the other components include a water-soluble polymer other than Component B, a pH adjuster other than Component C, a preservative, an alcohol, a chelating agent, an oxidizing agent, and the like.

[0065] [pH] The pH of the polishing liquid composition of the present disclosure is more than 8.5, preferably 9 or more, more preferably 9.5 or more, and more preferably 10 or more, from the viewpoint of improving the filter passing amount of the polishing liquid composition containing silica particles and the surface quality of the silicon substrate after polishing, and from the same viewpoint, it is 14 or less, preferably 13 or less, more preferably 12.5 or less, more preferably 12 or less, more preferably 11.5 or less, and more preferably 11 or less. From the same viewpoint, the pH of the polishing liquid composition of the present disclosure is more than 8.5 to 14 or less, preferably 9 to 13 or less, more preferably 9.5 to 12.5 or less, more preferably 9.5 to 12 or less, more preferably 9.5 to 11.5 or less, and more preferably 10 to 11 or less. The pH of the polishing liquid composition of the present disclosure can be adjusted using component C or a known pH adjuster. In the present disclosure, the above pH is a value measured by the method described in the Examples.

[0066] [pH-pKa] From the viewpoint of improving the filter passing amount of the polishing liquid composition containing silica particles and from the viewpoint of improving the surface quality of the polished silicon substrate, the pH of the polishing liquid composition of the present disclosure is preferably higher than the pKa of component B. From the same viewpoint, the difference between the pH and the pKa (pH-pKa) is 2 or more, preferably 2.5 or more, more preferably 3 or more, and from the same viewpoint, preferably 7 or less, more preferably 6 or less, even more preferably 5.5 or less, even more preferably 5 or less, even more preferably 4.5 or less, even more preferably 4 or less, and even more preferably 3.5 or less.

[0067] The polishing liquid composition of the present disclosure can be produced, for example, by blending component A and component B, and, if desired, water, component C, and other components by a known method. That is, the polishing liquid composition of the present disclosure can be produced, for example, by blending at least component A and component B. Therefore, in another aspect, the present disclosure relates to a method for producing a polishing liquid composition, which includes a step of blending at least component A and component B. In the present disclosure, "blending" includes mixing component A, component B, and, if necessary, water, component C, and other components simultaneously or in any order. The blending can be performed using, for example, a stirrer such as a homomixer, a homogenizer, an ultrasonic disperser, a wet ball mill, or a bead mill. The preferred blending amount of each component in the method for producing a polishing liquid composition of the present disclosure can be the same as the preferred content of each component in the polishing liquid composition of the present disclosure described above.

[0068] In the present disclosure, "the content of each component in the polishing liquid composition" refers to the content of each component at the time of use, that is, at the time when the polishing liquid composition is started to be used for polishing.

[0069] The polishing liquid composition of the present disclosure may be produced as a concentrate from the viewpoint of storage and transportation, and diluted at the time of use. The dilution ratio is preferably 2 times or more, more preferably 10 times or more, even more preferably 30 times or more, and even more preferably 50 times or more from the viewpoint of production and transportation costs, and is preferably 180 times or less, more preferably 140 times or less, even more preferably 100 times or less, and even more preferably 70 times or less from the viewpoint of storage stability. The polishing liquid composition concentrate of the present disclosure can be used by diluting with water so that the content of each component at the time of use is the above-mentioned content (i.e., the content at the time of use). In the present disclosure, the "time of use" of the polishing liquid composition concentrate refers to the state in which the polishing liquid composition concentrate is diluted.

[0070] [Polishing liquid kit] In another aspect, the present disclosure relates to a polishing liquid kit for producing the polishing liquid composition of the present disclosure (hereinafter, also referred to as the "kit of the present disclosure"). According to the kit of the present disclosure, a polishing liquid composition that can improve the amount of the polishing liquid composition containing silica particles passing through a filter and the surface quality of a silicon substrate after polishing can be obtained. In one or more embodiments, the kit of the present disclosure may be a polishing liquid kit containing a solution containing component A, component B, and component C. The solution may contain other components as required. The solution may be diluted with water as required at the time of use.

[0071] [Method of manufacturing semiconductor substrate] In another aspect, the present disclosure relates to a method for manufacturing a semiconductor substrate (hereinafter also referred to as the "semiconductor substrate manufacturing method of the present disclosure"), comprising a step of polishing a silicon substrate to be polished using the polishing method of the present disclosure (hereinafter also referred to as the "polishing step"), and a step of cleaning the polished silicon substrate (hereinafter also referred to as the "cleaning step"). In another aspect, the present disclosure relates to a method for producing a semiconductor substrate, comprising carrying out the method of the present disclosure, i.e., the method for improving a filter flow rate of the present disclosure, the method for improving a surface quality of a polished silicon substrate of the present disclosure, and / or the polishing method of the present disclosure. According to the semiconductor substrate manufacturing method disclosed herein, by using the polishing liquid composition disclosed herein, the filter passing amount of the polishing liquid composition containing silica particles and the surface quality of the polished silicon substrate can be improved, so that high-quality semiconductor substrates can be manufactured at high yield, high productivity, and low cost.

[0072] The polishing step in the semiconductor substrate manufacturing method of the present disclosure can include, for example, a lapping (rough polishing) step of planarizing a single crystal silicon substrate obtained by slicing a single crystal silicon ingot into a thin disk shape, and a finish polishing step of etching the lapped single crystal silicon substrate and then mirror-finishing the surface of the single crystal silicon substrate. The polishing liquid composition of the present disclosure is more preferably used in the finish polishing step from the viewpoint of improving the filter-passing amount of the polishing liquid composition containing silica particles and from the viewpoint of improving the surface quality of the silicon substrate after polishing.

[0073] The polishing step in the semiconductor substrate manufacturing method of the present disclosure can be performed under the same conditions (polishing pressure, polishing liquid composition, surface temperature of polishing pad, etc.) as those in the polishing step in the polishing method of the present disclosure described above.

[0074] In one or more embodiments, the method for producing a semiconductor substrate according to the present disclosure may include a dilution step of diluting a concentrate of the polishing liquid composition according to the present disclosure prior to the polishing step. The dilution medium may be, for example, water.

[0075] In the cleaning step in the semiconductor substrate manufacturing method of the present disclosure, it is preferable to perform inorganic cleaning from the viewpoint of reducing residues on the silicon substrate surface. Examples of the cleaning agent used in inorganic cleaning include inorganic cleaning agents containing at least one selected from hydrogen peroxide, ammonia, hydrochloric acid, sulfuric acid, hydrofluoric acid, and ozone water.

[0076] In one or a plurality of embodiments, the semiconductor substrate manufacturing method of the present disclosure can further include, after the cleaning step, a step of rinsing the cleaned silicon substrate with water and drying it. EXAMPLES

[0077] The present disclosure will be described in more detail below with reference to examples, but these are merely illustrative and the present disclosure is not limited to these examples.

[0078] 1. Preparation of Polishing Composition (Examples 1 to 7 and Comparative Examples 1 to 6) Silica particles (component A) shown in Table 1, a water-soluble polymer (component B or non-component B) shown in Table 1, ammonia (component C), and ultrapure water were mixed with stirring to obtain a concentrated solution of a polishing liquid composition (pH 10.6 to 11.0 (25°C)). The concentrated solution was diluted 60 times with ion-exchanged water to obtain the polishing liquid compositions of Examples 1 to 7 and Comparative Examples 1 to 6. The content of each component in Table 1 is the content of each component (mass % or mass ppm, active content) at the time of use of the polishing liquid composition. The content of ultrapure water is the remainder excluding component A and component B or non-component B and component C. The pH of each polishing liquid composition (at the time of use) at 25°C was 10.3. The pH at 25° C. was measured using a pH meter (Toa Denpa Kogyo Co., Ltd., HM-30G), and was the value measured one minute after immersing the electrodes of the pH meter in the polishing composition or a concentrate thereof.

[0079] The following Component A, Component B, Non-Component B, and Component C were used in the preparation of each polishing composition. (Component A) Colloidal silica [average primary particle size 35 nm, average secondary particle size 70 nm, degree of association 2.0] (Component B) B1: Methyldiallylamine-sulfur dioxide copolymer [Nittobo Medical Co., Ltd., weight average molecular weight 3,000] B2: Glycidol-modified polyallylamine, modification ratio 2.0 [manufactured by Nittobo Medical Co., Ltd., weight average molecular weight 11,000] B3: Glycidol-modified polyallylamine, modification ratio 1.8 [manufactured by Nittobo Medical Co., Ltd., weight average molecular weight 10,000] B4: Glycidol-modified polyallylamine, modification ratio 1.5 [manufactured by Nittobo Medical Co., Ltd., weight average molecular weight 8,900] B5: Glycidol-modified polyallylamine, modification ratio 1.0 [Nittobo Medical Co., Ltd., weight average molecular weight 6,900] (Non-ingredient B) B6: Allylamine (free) polymer [Nittobo Medical PAA-03, weight average molecular weight 3,000] B7: Hydroxyethyl cellulose (HEC) [manufactured by Daicel Corporation, SE400, weight average molecular weight 250,000] B8: Cationic polyvinyl alcohol (c-PVA) [Kuraray Co., Ltd., CM-318, weight average molecular weight 25,000] B9: Polyhydroxyethylacrylamide (pHEAA) 150g of hydroxyethylacrylamide (1.30mol, KJ Chemicals) was dissolved in 100g of ion-exchanged water to prepare an aqueous monomer solution. Separately, 0.035g of 2,2'-azobis(2-methylpropionamidine)dihydrochloride (polymerization initiator, "V-50", 1.30mmol, Wako Pure Chemical Industries, Ltd.) was dissolved in 70g of ion-exchanged water to prepare an aqueous polymerization initiator solution. After 1,180g of ion-exchanged water was put into a 2L separable flask equipped with a Dimroth condenser, a thermometer, and a crescent-shaped Teflon (registered trademark) stirring blade, the atmosphere in the separable flask was replaced with nitrogen. Next, the temperature in the separable flask was raised to 68°C using an oil bath, and the above-mentioned aqueous monomer solution and the above-mentioned aqueous polymerization initiator solution, which had been prepared in advance, were each dropped into the separable flask with stirring for 3.5 hours. After the dropwise addition was completed, the temperature and stirring of the reaction solution were maintained for 4 hours to obtain 1,500 g of a colorless, transparent, 10% by mass aqueous solution of polyhydroxyethylacrylamide (pHEAA, weight average molecular weight: 700,000). B10: Polyglycerin [Daicel's "XPW", polymerization degree 40, weight average molecular weight 3,000] B11: Polyvinyl alcohol (PVA) [Kuraray Co., Ltd., PVA105, polymerization degree: 500, weight average molecular weight: 25,000] (Component C) Ammonia [28% by weight ammonia water, Kishida Chemical Co., Ltd., special grade reagent]

[0080] 2.Measuring methods for various parameters (1) Measurement of the average primary particle size of silica particles (component A) The average primary particle size (nm) of component A is calculated by the BET (nitrogen adsorption) method. 2 / g) using the following formula: Average primary particle diameter (nm)=2727 / S

[0081] The specific surface area S of component A was measured by carrying out the following [pretreatment], and then weighing out approximately 0.1 g of the measurement sample into a measurement cell to four decimal places, drying the sample for 30 minutes in an atmosphere at 110°C immediately before measuring the specific surface area, and then measuring the specific surface area by the nitrogen adsorption method (BET method) using a specific surface area measuring device (Micromeritic automatic specific surface area measuring device "Flowsorb III2305", manufactured by Shimadzu Corporation). [Preprocessing] (a) The pH of the slurry of component A is adjusted to 2.5±0.1 with an aqueous solution of nitric acid. (b) The slurry of component A, adjusted to pH 2.5±0.1, is placed in a petri dish and dried in a hot air dryer at 150°C for 1 hour. (c) After drying, the obtained sample is finely ground in an agate mortar. (d) The ground sample is suspended in ion-exchanged water at 40°C and filtered through a membrane filter with a pore size of 1 μm. (e) The residue on the filter is washed five times with 20 g of ion-exchanged water (40°C). (f) The filter with the filtrate attached thereto is placed in a petri dish and dried in an atmosphere at 110°C for 4 hours. (g) The dried filtrate (component A) was taken, being careful not to mix in any filter debris, and finely ground in a mortar to obtain a measurement sample.

[0082] (2) Average secondary particle size of silica particles (component A) The average secondary particle diameter (nm) of component A was measured by adding an abrasive to ion-exchanged water so that the concentration of component A was 0.25 mass%, and then placing the resulting aqueous dispersion in a disposable sizing cuvette (a 10 mm polystyrene cell) to a height of 10 mm from the bottom, and using a dynamic light scattering method (apparatus name: Zetasizer Nano ZS, manufactured by Sysmex Corporation).

[0083] (3) Average particle size ratio d / d0 of silica particles (component A) Average particle diameter d The average particle diameter d of component A was measured using a dynamic light scattering method (apparatus name: "Zetasizer Nano ZS", manufactured by Sysmex Corporation) after pouring the polishing liquid composition shown in Table 1 into a disposable sizing cuvette (a 10 mm polystyrene cell) to a height of 10 mm from the bottom. Average particle diameter d0 The average particle diameter d0 of component A was measured using a dynamic light scattering method (apparatus name: "Zetasizer Nano ZS", manufactured by Sysmex Corporation) after pouring an aqueous dispersion obtained by removing component B from the polishing liquid composition in Table 1, i.e., an aqueous dispersion obtained by stirring and mixing the silica particles (component A), ammonia (component C), and ultrapure water shown in Table 1, into a disposable sizing cuvette (a 10 mm polystyrene cell) to a height of 10 mm from the bottom. Average particle size ratio d / d0 The average particle size ratio d / d0 was calculated using the obtained average particle size d and average particle size d0.

[0084] (4) Amount of component B adsorbed to component A The polishing composition prepared to have the contents shown in Table 1 was left to stand for 15 minutes. Then, a centrifugation process (25,000 rpm, 1 hour) was performed to separate the precipitate containing silica from the supernatant, and the TOC value of the supernatant was measured. Separately, a calibration curve was created from the TOC values ​​of aqueous solutions of component B at each concentration, and the amount of component B adsorbed to silica was calculated from this calibration curve and the TOC value of the supernatant.

[0085] (5) Measurement of filter passing volume The bottom of the cylindrical container (capacity 500 ml, inner upper diameter 9 cm, lower diameter 8 cm) had an opening that connected to the inside of the container. A tube connected to this opening was connected to a filter with a pore size of 0.2 μm and a filtration area of ​​4 cm via an on-off valve. 2 A filter [Advantec, hydrophilic PTFE 0.2 μm (pore size) filter, model: 25HP020AN] was connected. The upper cap of the cylindrical container had an opening communicating with the inside, and an air pump was connected to a tube connected to this opening via a pressure control valve. This cylindrical container was filled with 500 ml of the polishing composition shown in Table 1, and a constant air pressure (filtration pressure) of 0.25 MPa was applied to the inside of the cylindrical container. The open / close valve at the bottom of the cylindrical container was opened to allow the polishing composition to pass through the filter, and the amount of liquid passing through until the filter was clogged (g / sec cm 2 For polishing compositions that did not clog, the amount of polishing composition that passed through the filter until the interval between the polishing compositions passing through the filter became 5 seconds was defined as the amount of polishing composition that passed through the filter.

[0086] (6) Measurement of weight average molecular weight of water-soluble polymers (component B, non-component B) The weight average molecular weight of the water-soluble polymers (component B, non-component B) was calculated based on peaks in a chromatogram obtained by applying gel permeation chromatography (GPC) under the following conditions. <Method for measuring weight average molecular weight> The weight average molecular weight of the water-soluble polymer having an amino group (component B, non-component B) is a value calculated based on the peak in a chromatogram obtained by applying the gel permeation chromatography (GPC) method under the following conditions. Column: α-M + α-M Eluent: 0.15mol / L Na2SO4,1%CH3COOH / water Flow rate: 1.0mL / min Column temperature: 40℃ Detector: RI detector Standard substance: Pullulan (molecular weight: 788,000, 194,000, 47,300, 5900, all manufactured by Shodex)

[0087] The weight average molecular weight of the polymer compounds other than those mentioned above is a value calculated based on a peak in a chromatogram obtained by applying a gel permeation chromatography (GPC) method under the following conditions. Equipment: HLC-8320 GPC (Tosoh Corporation, detector integrated) Column: GMPWXL+GMPWXL (anion) Eluent: 0.2M phosphate buffer / CH3CN=9 / 1 Flow rate: 0.5mL / min Column temperature: 40℃ Detector: Shodex RI SE-61 differential refractive index detector Standard: Monodisperse polyethylene glycol with known molecular weight

[0088] (7) pKa measurement Using a HM-41K pH meter (Toa DKK Co., Ltd.), an aqueous solution of component B adjusted to 1 M was subjected to potentiometric titration at room temperature with 0.1 M hydrochloric acid. The pKa was calculated from the obtained titration curve.

[0089] (8) Glycidol modification rate The glycidol modification rate is 13 The carbon-carbon NMR spectroscopy was used to determine the <Measurement conditions> Sample: 200 mg of glycidol-modified polyallylamine dissolved in 0.6 mL of heavy water Equipment used: 400MHz 13 C-NMR (Agilent Technologies, Inc. "Agilent 400-MR DD2") Measurement conditions: 13 C-NMR measurement, pulse interval time 5 seconds, tetramethylsilane as standard peak (σ: 0.0 ppm) Accumulation count: 5000 times Each peak range used for integration: A: 71.0 to 72.3 ppm (integral value of the peak of C bound to the secondary hydroxyl group of glycidol reacted with amino group) B: 32.0 to 41.0 ppm (integrated value of the peak of the main chain C of allylamine) <Glycidol modification rate> The glycidol modification rate (ratio of glycidol equivalents to amino group equivalents) is calculated using the following formula. Glycidol modification rate (equivalent ratio) = 2A / B

[0090] 3. Evaluation of polishing using the polishing compositions of Examples 1 to 7 and Comparative Examples 1 to 6 (1) Polishing method Each polishing composition was filtered with a filter (compact cartridge filter "MCP-LX-C10S", manufactured by Advantec Co., Ltd.) immediately before polishing, and the following silicon substrates were subjected to finish polishing under the following polishing conditions. <Silicon substrate to be polished> Single crystal silicon substrate [single-sided mirror-finished silicon substrate with a diameter of 200 mm, conductivity type: P, crystal orientation: 100, resistivity: 0.1 Ω·cm or more but less than 100 Ω·cm] The single crystal silicon substrate was previously subjected to rough polishing using a commercially available polishing composition (GLANZOX 1302, manufactured by Fujimi Inc.). After rough polishing, the single crystal silicon substrate was subjected to finish polishing, and had a haze of 2 to 3 ppm.

[0091] <Finish polishing conditions> Polishing machine: Single-sided 8-inch polishing machine "GRIND-X SPP600s" (manufactured by Okamoto Kogyo) Polishing pad: Suede pad (manufactured by Toray Co., Ltd., Asker hardness: 64, thickness: 1.37 mm, nap length: 450 μm, opening diameter: 60 μm) Silicon substrate polishing pressure: 100g / cm 2 Plate rotation speed: 60 rpm Polishing time: 5 minutes Supply rate of polishing composition: 150 g / min Temperature of the polishing composition: 23°C Carrier rotation speed: 62 rpm

[0092] (2) Cleaning method After the finish polishing, the silicon substrate was subjected to ozone cleaning and dilute hydrofluoric acid cleaning as follows. In the ozone cleaning, an aqueous solution containing 20 ppm ozone was sprayed from a nozzle at a flow rate of 1 L / min toward the center of the silicon substrate rotating at 600 rpm for 3 minutes. The temperature of the ozone water was kept at room temperature. Next, dilute hydrofluoric acid cleaning was performed. In the dilute hydrofluoric acid cleaning, an aqueous solution containing 0.5 mass% ammonium hydrogen fluoride (special grade, Nacalai Tesque, Inc.) was sprayed from a nozzle at a flow rate of 1 L / min toward the center of the silicon substrate rotating at 600 rpm for 6 seconds. The above ozone cleaning and dilute hydrofluoric acid cleaning were performed as one set, for a total of two sets, and finally spin drying was performed. In the spin drying, the silicon substrate was rotated at 1,500 rpm.

[0093] (3) Evaluation of surface defects (LPD) on silicon substrates To evaluate the surface roughness (haze) of the silicon substrate surface after cleaning, the value (DWO haze) measured in the dark-field wide grazing incidence channel (DWO) using a surface roughness measuring device "Surfscan SP1-DLS" (KLA Tencor) was used. In addition, surface defects (LPD) were measured at the same time as the haze measurement, and were evaluated by counting the number of particles with a particle size of 45 nm or more on the silicon substrate surface. The smaller the value of surface defects (LPD), the fewer the surface defects. The surface defect (LPD) measurement was performed on two silicon substrates each, and the average value was calculated. The results are shown in Table 1.

[0094] [Table 1]

[0095] As shown in Table 1, it was found that the polishing compositions of Examples 1 to 7 were able to improve the filter passing amount and reduce surface defects on the silicon substrate compared to the polishing compositions of Comparative Examples 1 to 6. [Industrial Applicability]

[0096] The method of the present disclosure can improve the amount of liquid passing through a filter and reduce surface defects on a silicon substrate, and is therefore particularly useful as a method used in the manufacturing process of a silicon substrate.

Claims

1. A method for improving the amount of a polishing composition containing silica particles passing through a filter with a pore size of 0.2 μm, comprising the steps of: The method includes preparing a polishing composition comprising blending silica particles (component A) and an amino group-containing water-soluble polymer (component B), the composition having a pH of more than 8.5 and not more than 14, and a difference between the pKa of component B and the pH (pH-pKa) of 2 or more; Component A is colloidal silica, having an average primary particle size of 10 nm or more and 50 nm or less, an average secondary particle size of 20 nm or more and 100 nm or less, and a degree of association (=average secondary particle size / average primary particle size) of 1.1 or more and 3 or less, The component B is at least one of an amino group-containing water-soluble polymer containing an allylamine-derived structural unit (component B1) and an amino group-containing water-soluble polymer containing a diallylamine-derived structural unit (component B2), The component B1 is a copolymer in which at least a part of the amino groups in the structural unit derived from allylamine has a modified group with a glycidol derivative, The method, wherein the component B2 comprises a diallylamine-derived building block and a sulfur dioxide-derived building block.

2. 1. A method for improving surface quality of a polished silicon substrate, comprising: The method includes polishing a silicon substrate to be polished using a polishing composition that contains silica particles (component A) and an amino group-containing water-soluble polymer (component B), has a pH of more than 8.5 and not more than 14, and has a difference between the pKa of component B and the pH (pH-pKa) of 2 or more; Component A is colloidal silica, having an average primary particle size of 10 nm or more and 50 nm or less, an average secondary particle size of 20 nm or more and 100 nm or less, and a degree of association (=average secondary particle size / average primary particle size) of 1.1 or more and 3 or less, The component B is at least one of an amino group-containing water-soluble polymer containing an allylamine-derived structural unit (component B1) and an amino group-containing water-soluble polymer containing a diallylamine-derived structural unit (component B2), The component B1 is a copolymer in which at least a part of the amino groups in the structural unit derived from allylamine has a modified group with a glycidol derivative, The method, wherein the component B2 comprises a diallylamine-derived building block and a sulfur dioxide-derived building block.

3. A method for polishing a silicon substrate, comprising a step of polishing a silicon substrate using a polishing composition, comprising: a polishing composition comprising silica particles (component A) and an amino group-containing water-soluble polymer (component B), having a pH of more than 8.5 and not more than 14, and a difference between the pKa of component B and the pH (pH-pKa) of 2 or more; Component A is colloidal silica, having an average primary particle size of 10 nm or more and 50 nm or less, an average secondary particle size of 20 nm or more and 100 nm or less, and a degree of association (=average secondary particle size / average primary particle size) of 1.1 or more and 3 or less, The component B is at least one of an amino group-containing water-soluble polymer containing an allylamine-derived structural unit (component B1) and an amino group-containing water-soluble polymer containing a diallylamine-derived structural unit (component B2), The component B1 is a copolymer in which at least a part of the amino groups in the structural unit derived from allylamine has a modified group with a glycidol derivative, The method, wherein the component B2 comprises a diallylamine-derived building block and a sulfur dioxide-derived building block.

4. The method according to any one of claims 1 to 3, wherein the pKa of component B is 5 or more and 8.5 or less.

5. Average particle size ratio d / d of silica particles 0 The method according to any one of claims 1 to 4, wherein is less than or equal to 1.

1. d: average particle size of silica particles in the polishing composition d 0 Average particle size of silica particles in the polishing composition having the same pH value, except that the amino group-containing water-soluble polymer is removed from the polishing composition.

6. A method according to any one of claims 1 to 5, wherein the pH of the polishing composition is 9.5 or more and 12 or less.

7. The method according to claim 1 , wherein the content of Component A in the polishing composition is 0.05 mass % or more and 0.5 mass % or less.

8. The method according to claim 1 , wherein the content of Component B in the polishing composition is 10 ppm by mass or more and 200 ppm by mass or less.

9. The method according to claim 1 , wherein a ratio of a content of component B to a content of component A in the polishing composition is 0.008 or more and 0.2 or less.

10. 10. A method for manufacturing a semiconductor substrate, comprising: polishing a silicon substrate to be polished by using the polishing method according to claim 3; and cleaning the polished silicon substrate.

11. A polishing composition comprising silica particles (component A) and an amino group-containing water-soluble polymer (component B), having a pH of more than 8.5 and not more than 14, and a difference between the pKa of component B and the pH (pH-pKa) of 2 or more, Component A is colloidal silica, having an average primary particle size of 10 nm or more and 50 nm or less, an average secondary particle size of 20 nm or more and 100 nm or less, and a degree of association (=average secondary particle size / average primary particle size) of 1.1 or more and 3 or less, The component B is at least one of an amino group-containing water-soluble polymer containing an allylamine-derived structural unit (component B1) and an amino group-containing water-soluble polymer containing a diallylamine-derived structural unit (component B2), The component B1 is a copolymer in which at least a part of the amino groups in the structural unit derived from allylamine has a modified group with a glycidol derivative, The polishing composition, wherein the component B2 contains a constitutional unit derived from diallylamine and a constitutional unit derived from sulfur dioxide.

12. Average particle size ratio d / d of silica particles 0 The polishing composition according to claim 11, wherein the abrasive grain size is 1.1 or less. d: average particle size of silica particles in the polishing composition d 0 Average particle size of silica particles in the polishing composition having the same pH value, except that the amino group-containing water-soluble polymer is removed from the polishing composition.

Citation Information

Patent Citations

  • Polishing composition

    JP2008252022A

  • Polishing liquid composition for silicon wafer

    JP2011171689A

  • Polishing liquid composition for silicon wafers

    JP2015109423A

  • Colloidal silica and composition for polishing semiconductor wafer containing the same

    JP2016020294A

  • Aqueous silica slurry compositions for use in shallow trench isolation and methods of using them

    JP2019036712A